STRATEGI BERSAING PADA SENTRA INDUSTRI ANYAMAN MENDONG DI KABUPATEN TASIKMALAYA - Iis Miati; Rudi Setiawan (FEB Universitas Sam Ratulangi Manado, 2022)
ABSTRACT Mendong woven products are one of the superior products from Tasikmalaya Regency. This Mendong handicraft product has its own specialties because it has designs that follow the trend, the materials used are soft and look elegant. However, the mendong woven industry in Tasikmalaya Regency still has weaknesses that hinder the development of the industry even though in the production process it has followed various trends and product designs but still looks similar to all similar industry players. The purpose of this study was to find out about the competitive strategies used by mendong woven industries in Tasikmalaya Regency, seen from the SWOT Analysis strategy, and TOWS. The study used a qualitative approach with descriptive methods. Sources of information in this study were people who knew firsthand about the existence of the mendong woven industry such as from the Kabid of Tasikmalaya Regency, and the owner of the mendong woven industry in Tasikmalaya Regency. the EFAS calculation result is 0.72 and the IFAS calculation is 1, this shows that the mendong woven industry in Kab. Tasikmalaya is in the first quadrant, which means the industry is in the growth stage. Positive conditions from internal and external factors become a strong foundation for developing the mendong woven industry in Kab. Tasikmalaya. The growth that occurred in this industry was supported by stronger internal conditions compared to external conditions. Therefore, internal factors need to be considered to be the basis for maintaining the positive development of the mendong woven industry in Tasikmalaya Regency Keywords: Competitive Strategy, Industry, Crafts, Products, Mendong Weaving